A Validated RP-HPLC Method for the Determination of Atazanavir in Pharmaceutical Dosage Form - K. Srinivasu; J. Venkateswara Rao; N. Appala Raju; K. Mukkanti (E-Journal of Chemistry)
A validated RP HPLC method for the estimation of atazanavir in capsule dosage form on YMC ODS 150 × 4.6 mm, 5 μ column using mobile phase composition of ammonium dihydrogen phosphate buffer (pH 2.5) with acetonitrile (55:45 v/v). Flow rate was maintained at 1.5 mL/min with 288 nm UV detection. The retention time obtained for atazanavir was at 4.7 min. The detector response was linear in the concentration range of 30 - 600 μg/mL. This method has been validated and shown to be specific, sensitive, precise, linear, accurate, rugged, robust and fast. Hence, this method can be applied for routine quality control of atazanavir in capsule dosage forms as well as in bulk drug.